Striking the right balance between site and landscape-scale conservation actions for a woodland insect within a highly fragmented landscape: A landscape genetics perspective. (March 2016) - Watts, Kevin; Vanhala, Tytti; Connolly, Thomas; Cottrell, Joan
Abstract: Landscape-scale conservation is increasingly seen as an effective strategy to combat habitat loss and fragmentation. However, there is debate on the relative merit and balance between site and landscape-scale conservation actions. Here, we provide much needed evidence to inform this debate. Our study, set in the highly fragmented landscape of the Isle of Wight, Southern England, focuses on the wood cricket ( Nemobius sylvestris ), a poorly dispersing woodland specialist. We use a landscape genetics approach, combining evidence from microsatellite DNA variation with an analysis of the contemporary landscape. Results revealed impacts of fragmentation in the form of high genetic differentiation and restricted gene flow between woodlands. Despite this, we found low relatedness, high genetic diversity and little evidence of inbreeding or bottlenecking. Our study also revealed that the present day landscape has only a limited role in explaining the observed genetic pattern. These results indicate that conservation actions for this study species should focus primarily on site-based activities to improve habitat quality and maintain large populations. However, we acknowledge that many other species that operate over larger spatial scales and have much smaller populations may be far more susceptible to habitat fragmentation and may benefit from wider landscape-scale actions. We demonstrate the utility and challenges of using landscape genetics to inform conservation strategies and we highlight the need to strike a balance between site and landscape-scale actions. Furthermore, our results suggest a blanket adoption of landscape-scale conservation strategies, no matter how appealing, may in practice be a poor use of conservation resources. Graphical abstract: Highlights: We study a woodland insect in a highly fragmented landscape to inform conservation. Using landscape genetics we reveal strong evidence of fragmentation with restricted gene flow. Our species displayed low relatedness, high genetic diversity and limited signs of inbreeding or bottlenecking. Conservation of our species should focus on site-based activities to improve habitat quality and maintain large populations. Species that exist as small populations across larger spatial scales may however benefit from wider landscape-scale actions.